RETRACTED ARTICLE: Application of stable isotope analysis methods for reconstructing paleoenvironment and paleoclimate in sediment cores - Quan, Dang Minh; Nguyen, Pham Thao; Dung, Luu Viet; Quy, Tran Dang; Tue*, Nguyen Tai (Vietnam Journal of Earth Sciences, 2017)
This article has been retracted due to the quality, at the request of the editors-in-chief. The Publisher apologizes for any inconvenience this may cause.